Prediction of the correct firing position with a pistol based on a MANFIS model. - Chicaiza Conterón, Luis Armando (2023)
Simulator systems are intended to facilitate access to practice in dif ferent test environments through a closed environment using computer vision. In this paper, a MANFIS model is implemented to improve the position of a trainee through positioning practice, which is responsible for detecting and displaying the errors that the trainee has when adopting the shooting position in real time. This environment qualifies, evaluates the pistol shooting position in a closed en vironment, analyzes, compares, and discusses the results obtained to determine the best option for evaluating the shooting position where the integrity and safety of the practitioner are paramount. The programs are adjusted to the process of identification and evaluation by Computer Vision using algorithms and pro cessing methods. The evaluation reached an overall efficiency 89.59 ± 3.36%, for 12 participants, determining the virtual simulator as adequate for training practices of the correct firing position.